Time-domain performance of QBC with self-lift circuit - Ramamurthi, Subbulakshmy; Velmurugan, Palani; Devendiren, Shobana; Manivannan, Soundarapandiyan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This study examines the performance of a high-gain quadratic boost converter (QBC) coupled with a self-lift circuit under two control methodologies: sliding mode control (SMC) and fractional-order proportional integral derivative (FOPID) control. The QBC topology is used because it can boost voltage significantly, which is especially useful for renewable energy applications. Simulation studies show that both controllers can control the output voltage of the converter, but the FOPID controller works better in dynamic situations. In particular, it makes settling happen faster, cuts down on overshoot, and lowers steady-state error compared to the SMC method. The overall results show that the FOPID controller is a good choice for improving stability and transient response. This makes it a good choice for advanced high-performance power electronic systems.